This can still be Europe's century - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2016)
We live in a world of black and white, with referenda in the yes/no style, politics in 100-second video clips and headline chasing. All of this leads to over-simplification and, in the end, to a seeming reduction of options. We see this all too well in the case of the European Union: one is either for or against it. In this cacophony of dichotomous beliefs and one-sided or even false information we tend to oversee the most important question: do we really want to leave behind what we have achieved in seven decades of a great European project? We still have a narrow window of opportunity to introduce reforms, but time is running out. With Euro-scepticism on the rise it becomes harder each day to tell a convincing and impassioned European story.
Keywords: 330